Capital de trabajo y desempeño financiero: tendencias y avances de investigación - García Narváez, Karla Patricia (Machala : Universidad Técnica de Machala, 2025)
This study conducts a bibliometric analysis of scientific literature published between 1965 and 2024 concerning the relationship between working capital and business profitability, aiming to identify its evolution, thematic structure, and collaboration networks. Using the Scopus database and tools such as VOSviewer and Miscrosoft Excel, 2.141 indexed articles were analyzed, revealing a sustained growth in publications since 2000, particularly in countries like the United States, India, and China. The findings show that efficient working capital management; especially in cash conversion cycles, accounts receivable, and accounts payable; directly impacts key performance indicators such as ROA and ROE, and is vital for profitability, liquidity, and financial sustainability, especially for SMEs in emerging economies. The analysis identified consolidated thematic clusters including “working capital management”, “profitability”, and “financial efficiency”, alongside emerging lines of research related to sustainability, digitalization, and financial inclusion. Despite the increased research output, there remains a concentration in specific geographic and thematic area, limiting visibility for underrepresented contexts. Collaboration networks show sings of increasing internationalization, although regional connections still prevail. The literature confirms the strategic importance of working capital as a tool to maximize value and minimize financial risk, highlighting the need for context-sensitive polices and sector-specific approaches. The study concludes that bibliometric methods not only enable a structured mapping of existing knowledge but also help identify thematic gaps and guide future research towards a more comprehensive understanding of the connection between operational financial management and sustainable business performance.
El presente estudio realiza un análisis bilbiométrico de la producción científica publicada entre 1965 y 2024 sobre la relación entre capital de trabajo y rentabilidad empresarial, con el fin de identificar su evolución, estructura temática y redes de colaboración. Mediante la base de datos Scopus y herramientas como VOSviewer y Microsoft Excel, se analizaron 2.141 atículos indexados, revelando un crecimiento sostenido de publicaciones desde el año 2000, especialmente en países como Estados Unidos, India y China. Se evidenció que la gestión eficiente del capital de trabajo; especialmente el manejo del ciclo de conversión de efectivo, cuentas por cobrar y por pagar; impacta directamente en indicadores como ROA y ROE, siendo clave para la rentabilidad, liquidez y sostenibilidad financiera, particularmente en PyMEs de economías emergentes. Las investigaciones identificaron clústeres temáticos consolidados como “working capital management”, “profitability” y “financial efficiency”, así como líneas emergentes vinculadas a sostenibilidad, digitalización e inclusión financiera. A pesar del aumento de estudios, persiste una concentración geográfica y temática que limita la visibilidad de contextos subrepresentados. Las redes de colaboración científica muestran una creciente internacionalización, aunque todavía predominan los vínculos regionales. La literatura confirma la relevancia del capital de trabajo como herramienta estratégica para maximizar valor y minimizar riesgo, destacando la necesidad de políticas adaptadas al contexto económico y sectorial. Se concluye que el enfoque bibliométrico permite no sólo mapear el conocimiento acumulado, sino también identificar vacios temáticos y orientar futuras investigaciones hacia una comprensión más integral del vinculo entre gestión financiera operativa y rendimiento empresarial sostenido.
Keywords: CAPITAL DE TRABAJO; RENTABILIDAD EMPRESARIAL; ANÁLISIS BIBLIOMÉTRICO; GESTIÓN FINANCIERA